Mark, a Pauline theologian a re-reading of the traditions of Jesus in the light of Paul's theology - Pérez i Díaz, Mar 1970-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2020)
Sind die zahlreichen Hinweise, die im Markusevangelium auftauchen und sich der paulinischen Theologie annähern, Zufall oder eher Absicht des Evangelisten, sein Werk mit den Gedanken des Apostels Paulus zu vereinen? Mar Pérez i Díaz plädiert dafür, dass Markus kein Jünger des Petrus ist, der schriftlich festhält, woran er sich aus dessen Lehre erinnert, sondern ein theologischer Jünger des Paulus.
The significance of the Evangelist Mark lies in the fact that he was able to write an autobiographical account of Jesus of Nazareth. It seems to have been the first account of this type; it is certainly the oldest text that has survived along with the letters of Paul. In this study, Mar Pérez i Díaz argues that Mark, rather than being a disciple of Peter who puts in writing what he remembers from his preaching, is a theological disciple of Paul. By analysing the Pauline and Marcan texts and the theological elements which converge, she shows that Paul's theology enhances our understanding of the narrative in Mark because it completes the meaning of the gospel and complements its intentionality. The wide range of evidence in the gospel cannot be the fruit of chance, but rather of the will of the Evangelist to unify his work with the thought of the Apostle Paul.
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Porträt Gottes; Cosmic Eschatology; Comma Johanneum; Wissenschaftliche Untersuchungen zum Neuen Testament 2. Reihe; Aramaic Background of New Testament; Kirchliche Loyalitätsobliegenheiten; Kirchliches Selbstbestimmungsrecht; Priestly Tradition; Paul; Pauline Christology; Mark; Pauline textual indication; Neues Testament; Kirchengeschichte; Array; Modern; Hochschulschrift